Kinetic and Thermodynamics Studies the Adsorption of Phenol on Activated Carbon from Rice Husk Activated by ZnCl2 - Andi Muhammad Anshar; Paulina Taba; Indah Raya (Indonesian Journal of Science and Technology, 2016)
The purpose of this study was to investigate the adsorption ability of activated carbon from rice husk in adsorbing phenol. Activated carbon used was in this studies burning risk husk at 300 and 400oC and then activated by 10% of ZnCl2. The from activated carbon was characterized using an Infrared Spectrometer, an X-ray diffraction, an Scanning Electron Microscope, and a gas sorption analyzer. The best activated carbon for adsorbing phenol was the activated carbon that prodused from the burning of rice husk at a temperature 400oC and activated with 10% of ZnCl2 for 24 hours. Adsorption capacity of the best activated carbon was 3.9370 mg/g adsorbent with Gibbs free energy of -25.493 kJ/mol.